2009
DOI: 10.1111/j.1651-2227.2008.01073.x
|View full text |Cite
|
Sign up to set email alerts
|

Children with chronic kidney disease: a 3‐year prospective study of growth, bone mass and bone turnover

Abstract: A normal BMD does not exclude mineral bone disorder in patients with CKD, yet the BMD Z-scores were well preserved and most markers of bone turnover were within the reference intervals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…Consistent with our findings, other studies have also reported significantly higher OPG levels in children on dialysis compared to controls [13,17]. Swolin-Eide et al [14][15][16], who reported OPG levels within the healthy reference intervals in pediatric patients with various stages of CKD, found that at the end of a 3-year follow-up almost 50% of them had OPG levels above the reference intervals. These authors hypothesized that a compensatory mechanism had developed in these patients for maintaining adequate bone mass; the concept of such a mechanism was supported by the normal bone mineral density of these patients [16].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Consistent with our findings, other studies have also reported significantly higher OPG levels in children on dialysis compared to controls [13,17]. Swolin-Eide et al [14][15][16], who reported OPG levels within the healthy reference intervals in pediatric patients with various stages of CKD, found that at the end of a 3-year follow-up almost 50% of them had OPG levels above the reference intervals. These authors hypothesized that a compensatory mechanism had developed in these patients for maintaining adequate bone mass; the concept of such a mechanism was supported by the normal bone mineral density of these patients [16].…”
Section: Discussionsupporting
confidence: 94%
“…In childhood, the interpretation of bone mineral measurements is more complex than in adults because of more dynamic changes in growing bones. In fact, studies regarding OPG [13][14][15][16][17] and RANKL [17,18] in the pediatric population with CKD are few, and no studies have assessed the relationship of the OPG/RANKL system with FGF-23. Findings from one animal study have shown that OPG may play a key role in mediating the response of FGF-23 to an oral phosphate load in bone cells [19].…”
Section: Abbreviationsmentioning
confidence: 99%
“…Most studies of bone health in pediatric CKD used DXA and yielded inconsistent results, reporting decreased [2832], normal [25, 3335], or increased BMD [36, 37] compared to controls. These studies utilized varying methods to adjust for growth failure and different reference samples to generate Z-scores.…”
Section: Discussionmentioning
confidence: 99%
“…This effect was illustrated in a study of pediatric renal transplant recipients: Areal BMD Z ‐scores relative to chronologic age were 1 to 2 SD lower than areal BMD Z ‐scores relative to height age 10. Accordingly, prior DXA studies in children with CKD yielded variable and inconsistent results, reporting decreased,11–16 normal,17–20 or increased15, 20–22 areal BMD compared with controls.…”
Section: Introductionmentioning
confidence: 99%